"REORDENAMIENTO, LINEAMIENTOS ARRIBA": LEGITIMACY AND POLITICAL CULTURE IN CUBA'S REFORM STRATEGY. (1st October 2012) - Unknown
Abstract : The Guidelines on Economic and Social Policy adopted by the Cuban Communist Party's 6th Congress in 2011 focus on the detail of economic policy, and have attracted political comment mainly in terms of the general implications for Cuban socialism of stronger market forces and a larger private sector. The 'updating' process, however, is not only political in terms of these implications, but also in terms of state legitimacy that may have more influence on the success of the 'updating' than economic expertise and profitability. This article addresses the legitimacy issue in terms of the impact of the public consultation on the Guidelines; in terms of the linked 're-ordering' of the workforce since 2010; and in terms of the severe critique of Cuba's elite political culture made in President Raúl Castro's keynote speeches on the updating process and on the Party's role at the 2012 Party Conference.